Aaron Temkin Beck (born July 18, 1921-) Biography - K. Fatih Yavuz; M. Hakan Türkçapar (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Aaron Beck was born in Providence, Rhode Island, USA, the youngest child of four siblings. Beck attended Brown University, graduating magna cum laude in 1942. Then he attended Yale Medical School, graduating with an M.D. in 1946. After his graduation, he served a rotating internship, followed by a residency in pathology at the Rhode Island Hospital. Although initially not interested in psychiatry, a residency in neurology at the Cushing Veterans Administration Hospital in Framingham, MA, required rotation in psychiatry intrigued him with some of the more recent developments in the field. He spent two years as a fellow at Austin Riggs Center at Stockbridge where he acquired substantial experience in conducting longterm psychotherapy. The Korean War shifted Beck’s area of work to the Valley Forge Army Hospital where he was Assistant Chief of Neuropsychiatry. Dr. Beck joined the Department of Psychiatry of the University of Pennsylvania in 1954. He initially conducted research into the psychoanalytic theories of depression. He developed a different theoretical-clinical approach that he labelled cognitive therapy. Since 1959 he has directed funded research investigations of the psychopathology of depression, suicide, anxiety disorders, panic disorders, alcoholism, drug abuse, personality disorders, and schizophrenia and of cognitive therapy of these disorders. Currently Aaron T. Beck, M.D., is the President Emeritus of the non-profit Beck Institute for Cognitive Therapy and Research, and University Professor in the Department of Psychiatry at the University of Pennsylvania and the director of the Psychopathology Research Unit (PRU), which is the parent organization of the Center for the treatment and Prevention of Suicide. He has published more than 550 scholarly articles and 18 books and has developed widely used assessment scales. He has received many prestigious awards including the 2006 Albert Lasker Clinical Medical Research Award for developing cognitive therapy, which fundamentally changed the way that psychopathology is viewed and its treatment is conducted. He has been listed as one of the “10 individuals who shaped the face of American Psychiatry” and one of the 5 most influential psychotherapists of all time by The American Psychologist (July 1989). [JCBPR 2012; 1(2.000): 77-80]